The austral-most record of the genus Haemagogus Williston (Diptera: Culicidae) - Obholz, Gisella Adriana (2020)
Introduction: The genus Haemagogus Williston is restricted to Central America and North and middle of South America and it includes numerous species of yellow fever virus vectors. Methods: Adult female and larvae mosquitoes were collected using hand aspirators and dipper and pipette, respectively. Results: The first record of a species of Haemagogus and particularly of Haemagogus spegazzinii was from La Pampa, Argentina. With this registry, the number of species found in La Pampa province rises to 18. Conclusions: New information on breeding sites for the species and implications of this new record suggest a possible extension of distribution in the near future.